Analysis of Risk Factors for Anemia among Adolescent Girls in Semarang City, Central Java, Indonesia - Adita Puspitasari Swastya Putri; Mateus Sakundarno Adi; Suhartono; Nurjazuli; Egy Sunanda Putra (Poltekita: Jurnal Ilmu Kesehatan, 2025)
Anemia remains a significant public health concern with detrimental effects on adolescent health. It is strongly influenced by both overall health status and dietary patterns. Adolescent girls are particularly vulnerable to anemia due to the rapid physical growth during puberty, which increase the need for nutritional intake. The prevalence of anemia among female students in Islamic Boarding School is much higher. They tend to to consume a diet that is less diverse and low in nutrients. The aim of this study is to determine the risk factors associated with anemia among adolescent girls in Semarang City, Central Java, Indonesia. This study used an observational analytic approach using a cross-sectional design. The research was conducted at Islamic Boarding School X in Semarang City in December 2024. The sample consisted of 55 adolescent girls selected through simple random sampling. Primary data were collected through laboratory examinations, physical examinations and interviews. Descriptive analysis was used to present frequency distributions, and bivariate analysis was performed to determine associations between variables. The results of this study from 55 respondents showed a relationship between BMI and the incidence of anemia among adolescent girls (p=0.05). There was no relationship between Z-Score, CED, energy intake, protein intake, fat intake, and carbohydrate intake with the incidence of anemia among adolescent girls (p=0.24; 0.29; 0.30; 0.73; 0.60; and 0.49, respectively). Adolescent girls with anemia are advised to maintain a healthy body weight by regular monitoring their of BMI alongside hemoglobin levels. A balanced and nutritious diet is essential to meet daily nutritional requirements and reduce the risk of anemia.